An industrial quality control study on Automated Technology Phil, Inc. - Bias, Maylyn; Bondoc, Mary Grace; Santos, Hannah Ruth. (Diliman, Quezon City College of Engineering, 2006)
Automated Technology Phil. Inc. is a prime local manufacturer of semiconductor chips. Due to high manufacturing cost, increased competition in the semiconductor market, and sensivitivity of IC's production, a good quality program is a must for the company. To assess the adequacy of the current quality program and address the problem of too many number of defectives in the final product, the group conducted a three-month long quality control study on the company. The study found out that in general, the quality standards of the company with respect to the number of outgoing product is still acceptable. However, some components of the quality system in some stages in the process are identified to have needs for improvement. In the inspection of wirebonded in process products, it was discovered that the process is incapable although it is in control. This may affect the production process since the variability in the process average would indicate that the machine is deteriorating because the machine is not producing uniform products. The management may conduct a machine control and monitoring study through statistical design of experiments and analysis of variance (ANOVA) to have a basis on machine replacement or maintenance. It was also advised that the management set a standard capability ratio for the machines so the operator can note whether the actual capability ratio reaches it. In addition, it was recommended for the company's statistical process control (SPC) software system to include the latter four sensitizing rules since they work well for small shifts. For the hipot testing and electrical testing that use an allowable fraction defective of 0.1, it was suggested that the company also implement the SPC in these processes in order to monitor the number of defectives per batch of produced ICs. In the latter period of the control chart implementation in these areas, it was also proposed that variable control charting be imposed especially to the electrical characteristics that accounts for more than 50 percent defectives so that more information regarding the process will be gathered. It would also be helpful if the standard allowable fraction of defectives is lowered to 0.5 since 0.10 is relatively large resulting to high production cost that was wasted and inefficient utilization of the company's resources. For the raw materials inspection, the acceptance sampling plan that uses an acceptance number of zero gives a rapid drop on the probability of acceptance of the incoming raw materials. This plan is sometimes hard for the supplier and extremely uneconomical for the consumer. If rejected lots are returned to the vendor, large number of lots will be unnecessarily returned that might result to production delays on the company. Chain sampling plan is then recommended. It makes use of the cumulative results of several preceding lots rejecting the lot when one defect is discovered. No defectives on the preceding three to five lots are preferred.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Automated Technology Philippines Incorporated; Semiconductor industries; Quality control